Pengaruh Self-Leadership, Work Ability, Burnout, Terhadap Ocb Dan Kinerja Pengajar Pada Bimbingan Belajar Di Surabaya - Charles Sidauruk; Laurentius ST Gomo Tumanggor; Siti Mujanah; Achmad Yanu Alif Fianto (Jurnal Pendidikan Indonesia, 2025)
his study aims to analyze the influence of self-leadership, work ability, and burnout on Organizational Citizenship Behavior (OCB) and teaching performance at tutoring institutions in Surabaya. Self-leadership focuses on an individual's ability to influence themselves to achieve optimal performance, while work ability encompasses physical, mental, and skill-related capacities in the workplace. Burnout, measured through emotional exhaustion, depersonalization, and reduced personal achievement, can affect OCB and teaching performance. This study employs a quantitative method by collecting data through questionnaires distributed to teachers at tutoring institutions in Surabaya. The results show that self-leadership and work ability have a significant impact on OCB and teaching performance, while burnout is found to reduce teaching performance. Furthermore, OCB is positively related to teaching performance. This research contributes significantly to understanding the factors affecting teaching performance and the importance of self-management and work environment conditions in enhancing teaching effectiveness.